2016
DOI: 10.1002/ceat.201500458
|View full text |Cite
|
Sign up to set email alerts
|

Optimized Stirred Reactor for Enhanced Particle Dispersion

Abstract: Homogeneous dispersion of particles is crucial for many processes where the reaction rate is highly dependent on relative rates of mixing or degree of homogenization. These processes include crystallization, polymerization, and some mineral-refining processes. Complete particle dispersion in high-concentration slurries is researched experimentally and numerically. Computation fluid dynamics results suggest that cloud height is an excellent indicator for mixing homogeneity, and energy efficiency can be enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
3
16
0
Order By: Relevance
“…For imaging in tubular continuous multiphase flow operations, multiple sensors along the length of the tube can be helpful for providing real‐time images and data like particle size distribution to evaluate and improve operating conditions such as feed flow rates and starting concentration/temperature. Due to the one‐to‐one relationship between batch and continuous tubular operations, e.g., the time operating in a batch process corresponds to the residence time in a tubular process, the spatial locations of these sensors can mimic the time profile for the batch process , . The total number of stereomicroscopes for continuous‐flow processes mimics the total sampling points for batches, but without having to drawing out samples.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For imaging in tubular continuous multiphase flow operations, multiple sensors along the length of the tube can be helpful for providing real‐time images and data like particle size distribution to evaluate and improve operating conditions such as feed flow rates and starting concentration/temperature. Due to the one‐to‐one relationship between batch and continuous tubular operations, e.g., the time operating in a batch process corresponds to the residence time in a tubular process, the spatial locations of these sensors can mimic the time profile for the batch process , . The total number of stereomicroscopes for continuous‐flow processes mimics the total sampling points for batches, but without having to drawing out samples.…”
Section: Resultsmentioning
confidence: 99%
“…Sampling is a helpful and standard experimental approach, but its drawbacks include yield reduction if the sample slurry is pulled out of the system, the increased potential for clogging if the sampling system is connected to the main crystallizer, and that the collected crystals may not be representative of the slurry. Commercial in situ imaging probes can provide real‐time crystal images with the probes inserted in the crystallizer (the working distance is less than the crystallizer wall thickness), at a high capital cost, typically $100 000 or more such as the particle vision measurement (PVM) . The measured crystals may not be representative of the slurry as well, and the introduction of new surfaces, e.g., of probe tips, to the crystallizer can also lead to increasing fouling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to maintain the given goals, process intensification appears to be one attractive strategy to notably minimize unit volume while keeping the productivity in the mineral refineries. The ultimate goal of process intensification was proposed to intensify the mixing units that deal with ultra-high concentration reactive and/or inert particles in complex fluids (Wang et al, 2012a(Wang et al, , 2012b(Wang et al, , 2016aWu et al, 2016). Ultra-high (fine) solids loadings tend to modify slurry viscosity and/or rheology, and recent experimental and theoretical analysis have showed that homogenization of high concentration slurries in the stirred reactors is rather difficult (Wang et al, 2012a(Wang et al, , 2012b(Wang et al, , 2016a.…”
Section: Mixing Of Suspension With High Concentration Solidsmentioning
confidence: 99%
“…Local conductivity [14] Aluminum hydroxide precipitation in aqueous solution by reaction of NaOH and Al(NO 3 (1) Color of the liquid phase estimated visually, (2) tracer concentration [11] Water, aqueous solution of polyvinylpyrrolidone (m = 12, 50 m Pa s), glass beads (d p = 0.09, 0.37, 1.5 mm)…”
Section: -7mentioning
confidence: 99%